Comparison of methodologies for seismic fragility analysis of unreinforced masonry buildings considering epistemic uncertainty. (15th February 2020) - Su, Liang; Li, Xi-long; Jiang, Yi-pang
Highlights: A systematic methodologies comparison for the parameter uncertainty analyses was Presented. Latin hyper sampling was proved to be the most practical method to consider epistemic uncertainty. Parameter uncertainty is non-negligible for the seismic fragility analysis of masonry structures. Abstract: The first-order second-moment (FOSM), Latin hypercube sampling (LHS), and Monte Carlo simulation (MC) methods were applied to perform seismic fragility analyses of unreinforced masonry (URM) buildings, incorporating incremental dynamic analysis (IDA). The epistemic uncertainty caused by parameter uncertainty was also considered by all three methods, which therefore obtained more accurate results compared with the conventional IDA analysis that only considers the aleatory uncertainty caused by the record-to-record variability. Nine structural parameters were selected as the epistemic uncertainty inputs, and the URM buildings were modeled by the equivalent frame models in OpenSees. The analysis results indicated that the epistemic uncertainty was non-negligible because of the high dispersion of the structural parameters and high nonlinearity of the seismic responses of the URM buildings. At the same time, the epistemic uncertainty values derived by LHS-IDA and MC-IDA were slightly larger than that derived by FOSM-IDA as a result of the consideration of the nonlinear response. In the final comparison, the LHS-IDA was proven to be the most efficient and accurate way to consider the influence of epistemic uncertainty.